الولاء التنظيمي وعلاقته بالرضا الوظيفي لدى أعضاء هيئة التدريس بجامعة دنقلا : دراسة ميدانية على عينة من أعضاء هيئة التدريس بجامعة دنقلا - محمد أحمد قمر مجذوب, أحمد (جامعة الوادي University of Eloued, 2015)
هدفت الدِّراسة إلى الكشف عن العلاقة بين الولاء التنظيميّ والرضا الوظيفيّ لدى أعضاء هيئة التّدريس بجامعة دنقلا، بالإضافة إلى تأثير بعض المتغيرات(النوع الاجتماعيّ، سنوات الخبرة والعمر، المؤهل العلميّ)، بلغت عينة الدِّراسة (100) عضواً، تم اختيار عينة الدِّراسة عن طريق العينة العشوائية الطبقية، تم تحليل البيانات باستخدام المتوسطات الحسابية والانحرافات المعيارية، واختبار(ت) وتحليل التباين، أظهرت النتائج: أن درجة الولاء التنظيمي والرضا الوظيفي لدى أعضاء هيئة التدريس جاءت بدرجة مرتفعة، لم تجد الدِّراسة علاقة ذات دلالة إحصائية بين الولاء التنظيمي والرضا الوظيفي، كذلك لا توجد فروق ذات دلالة إحصائية في الولاء التَّنظيمي والرضا الوظيفي تُعزى لمتغير النوع الاجتماعي، وأظهرت أيضاً وجود علاقة ذات دلالة إحصائية في الولاء التنظيمي والرضا الوظيفي تُعزى لمتغيرات سنوات الخبرة ولصالح (11) سنة فأكثر، وكذلك توجد فروق في الولاء التنظيمي تُعزى لمتغير المؤهل العلمي ولصالح المعيد، كما توجد فروق في الرضا الوظيفي تُعزى لمتغير العمر ولصالح أقل من(30) سنة، بينما لم تظهر فروق في الولاء التنظيمي تُعزى لمتغير العمر، والرضا الوظيفي تُعزى لمتغير المؤهل العلمي. Abstract: This study aimed at investigating of the relationship between Organizational commitment and Job satisfaction among staff members at Dongola University, and then to the effect of some variables, (Gender, years of experience, age, academic qualification). The sample of this study consisted of (100) staff members, year(2015), chosen by the stratified random, The data is then analyzed using mean, stander deviation, T-test, ANOVA. Results showed: organizational loyalty and job satisfaction was high degree. There is no statistically significant relationship between organizational loyalty and job satisfaction. Also no statistically significant differences in organizational loyalty and job satisfaction differences due to the variable gender, There are statistically significant in the organizational loyalty and job satisfaction due to the variable years of experience differences in favor of 11 years and over, There are also differences in organizational loyalty attributed to the educational qualification variable in favor of teaching assistant. There are also differences in job satisfaction due to the variable age in favor of less than 30 years, There are no differences in the organizational loyalty due to the variable age, and job satisfaction, academic qualification variable.
The relationship between organizational loyalty and job satisfaction among staff members at Dongola University
مقال- مجلة رؤى اقتصادية
Keywords: الولاية الشمالية، جامعة دنقلا، كلية التربية مروي; Northern State, Dongola University, Faculty of Education.